Anion exchange chromatography-based purification of plant-derived nanovesicles from Brassica oleracea L.: molecular profiling and bioactivity in human cells - Zanotti, Clarissa; Arena, Simona; De Pascale, Sabrina; Ciaravolo, Valentina; Ferracane, Rosalia; Troise, Antonio Dario; Pontecorvi, Chiara; Pacello, Francesca; Niespolo, Chiara; Gismondi, Angelo; Scaloni, Andrea; Marra, Mauro (Frontiers in Bioengineering and Biotechnology, 2025)
Plant-derived nanovesicles emerge as a promising alternative to mammalian-derived exosomes with distinct advantages, including lower immunogenicity, enhanced bioavailability, and the presence of bioactive plant metabolites. They have been shown to cross biological barriers, delivering therapeutic molecules that modulate gene expression, inflammation, oxidative stress, and cancer-related pathways. However, challenges remain that limit applicative use, including poor knowledge of their interactions with mammalian host cells and primarily the lack of a cost-effective and scalable method to obtain highly purified plant-derived nanovesicles. To address these limitations, we have developed an advanced purification platform that integrates ultrafiltration with anion exchange chromatography in a fast protein liquid chromatography system. This approach was validated using it in the isolation of plant-derived nanovesicles from Brassica oleracea L. seedlings, resulting in highly purified and concentrated preparations. Comprehensive molecular analyses, including proteomics, lipidomics, metabolomics, and miRNA profiling, characterized the nature of the purified plant-derived nanovesicles. Furthermore, their wound healing and anti-inflammatory properties were demonstrated in vitro and correlated to the potential biological activities of cargo miRNAs species by bioinformatics, highlighting the potential in nanomedicine of anion exchange-purified brassica nanovesicles. This study provides a scalable and efficient purification strategy, which might pave the way for broader applications of plant-derived nanovesicles in the clinical, nutraceutical and pharmaceutical fields.